2022
DOI: 10.1080/09064710.2022.2100819
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol activity of Bacillus , Paenibacillus and Pseudomonas against Fusarium wilt of chickpea in Morocco

Abstract: Fusarium wilt caused by Fusarium oxysporum f.sp ciceris is one of the major diseases impacting chickpea productivity. Significant losses are reported by farmers due to the absence of effective wilt management options. Biological control using beneficial microorganisms in agriculture, is one of the promising alternatives and eco-friendly strategies utilised to overcome this disease. The present study investigated the biocontrol effect of 40 bacterial strains isolated from the rhizosphere of healthy chickpea pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…ciceris. Elbouazaoui et al (2022) reported that 12 of 40 strains inhibited the growth of F. oxysporum f. sp. ciceris by more than 25% in vitro and found that the most antagonistic activity was caused by B. amyloliquefaciens and B. subtilis isolates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ciceris. Elbouazaoui et al (2022) reported that 12 of 40 strains inhibited the growth of F. oxysporum f. sp. ciceris by more than 25% in vitro and found that the most antagonistic activity was caused by B. amyloliquefaciens and B. subtilis isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Both in Turkey and worldwide, the main control methods used by farmers are short crop rotation with wheat and the use of chemical pesticides but their effectiveness in reducing disease inoculum in pathogen-infested soils is low (Elbouazaoui et al, 2022). Biological control is one of the best, most cost-effective, and environmentally sustainable methods of controlling plant diseases caused by soilborne pathogens such as Sclerotinia, Fusarium, Rhizoctonia, and Pythium spp.…”
Section: Introductionmentioning
confidence: 99%